Tibiofibular syndesmosis injury in an elite judo athlete, from diagnosis to treatment - a case report - Costa, C. M. M. P. (Universidade de Coimbra, 2025)
The tibiofibular syndesmosis is a fibrous joint that stabilizes the tibia and the fibula by its four ligaments, the anterior inferior tibiofibular ligament (AITFL), the posterior inferior tibiofibular ligament (PITFL), the interosseous ligament (IOL) and the transverse ligament (TL), preventing excessive movement between the two bones and maintaining structural integrity and mobility of the ankle.Injuries to the syndesmosis are clinically significant and usually result of high-impact trauma or torsional forces, common in contact sports.The injury of the tibiofibular syndesmosis can lead to chronic ankle instability and early degenerative changes, making the clinical evaluation of this structure and an accurate diagnosis crucial for initiating the appropriate treatment, especially in athletes. In this case report, a 27-year-old female judo athlete sustained a traumatic injury, characterised by a sprain of the right ankle. The patient exhibited symptoms including pain, functional limitation, and mild ankle swelling. Despite undergoing a three-week physiotherapy programme, the patient continued to experience pain and exhibited signs of joint instability. An MRI revealed moderate joint edema and a grade II syndesmosis injury. Following a six-month period of conservative treatment, the athlete was able to return to her previous competitive level without recurrence or the need for surgical intervention. Syndesmosis injuries constitute more than 15% of ankle sprains; however, they continue to be diagnosed late. An accurate and timely diagnosis is imperative for the provision of targeted treatment and the optimisation of recovery.A meticulous clinical report, inclusive of a precise description of the mechanism of injury and a thorough physical examination, constitutes the bedrock of an accurate diagnosis. The prevailing treatment strategy for such injuries is conservative, with surgical intervention being reserved for cases involving severe instability, associated fractures, or those that are unresponsive to conservative treatment.